2004
DOI: 10.1111/j.1944-9720.2004.tb02702.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of L2 Listening and Reading Comprehension by University Students Learning English in Korea

Abstract: This study compared L2 listening comprehension with L2 reading comprehension in terms of the roles of linguistic knowledge, background knowledge, and question types among 168 university students learning English in Korea. The analyses ojthe data found that L2 listeners processed inferential information more easily than factual information, while the reverse was true for L2 readers. In addition, linguistic and background knowledge exerted significant effects on L2 listening comprehension. In L2 reading comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 27 publications
5
42
1
Order By: Relevance
“…The results displayed that listening and reading skills had the highest correlation, but reading and writing skills had the least correlation. The finding regarding the close relationship between listening and reading is consistent with the results of some previous studies that have shown the share of their basic cognitive processes in language learning [33,38,39,41,42]. However, some [50][51][52] unanimously agree with the dissimilarity of listening and reading skills in terms of the receiving input to process the data.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results displayed that listening and reading skills had the highest correlation, but reading and writing skills had the least correlation. The finding regarding the close relationship between listening and reading is consistent with the results of some previous studies that have shown the share of their basic cognitive processes in language learning [33,38,39,41,42]. However, some [50][51][52] unanimously agree with the dissimilarity of listening and reading skills in terms of the receiving input to process the data.…”
Section: Discussionsupporting
confidence: 82%
“…It aligns with a theory suggesting that once a new written word is decoded phonologically, the link between phonology and semantics provides the meaning [35][36][37]. In addition to the central mutual comprehension between receptive skills, reading and listening, investigators such as Bae and Bachman [38], Park [39], Samuels [40], and Vandergrift [41,42] in the field agree upon the following similarities of the two skills. First, both entail fundamental language process and world knowledge and are engaged in comprehension as well as decoding.…”
Section: Listening and Reading Continuummentioning
confidence: 58%
“…First, there are lots of variables, which account for L2 acquisition, other than learning strategies such as linguistic knowledge, background knowledge, motivation, and acculturation (Ellis, 1994;Horwitz, 2008;Park, 2004). So, there will be limitation for one variable, say learning strategies, to account for L2 proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, listeners have a worse memory for spoken information than readers do for written information, with proportionally more details recalled by readers and proportionally more main ideas by listeners (Lund, 1991). Further, characteristics of the listener influence listening performance differently than they influence reading performance (Park, 2004). In addition, there are factors that are important to listening that are not relevant for reading, like coping with a fast speech rate and disfluencies.…”
Section: Introductionmentioning
confidence: 99%